Online Curves: A Quality Analysis of Scoliosis Videos on YouTube. Issue 23 (December 2015) - Staunton, Peter F.; Baker, Joseph F.; Green, James; Devitt, Aiden
Abstract : Study Design: A cross-sectional study. Objective: The aim of this study was to evaluate the quality of online scoliosis information available on the video sharing site YouTube. Summary of Background Data: The Internet is an increasingly utilized resource for accessing information about a variety of heath conditions. YouTube is a video sharing platform used to both seek and distribute information. Methods: A search for "scoliosis" was carried out using YouTube's search engine and data were collected on the first 50 videos returned. A JAMA score to determine currency, authorship, source and disclosure, and scoliosis-specific score that measures the amount of information on the diagnosis and treatment options (as devised by Mathur et al in 2005; scored 0–32) was recorded for each video to measure quality objectively. In addition, the number of views, number of comments, and feedback positivity was documented for each. Data analysis was conducted using R 3.1.4/R Studio 0.98 with control for the age of each video in analysis models. Results: The average number of views per video was 71, 152 with an average length of 7 minutes 32 seconds. Thirty-six percent of the videos fell under the authorship category of personal experience. The average JAMA score was 1.32/4 and average scoliosis specific score was 5.38/32. There was a positive correlation between JAMA score and number of views ( P = 0.003). However, in contrast, there was a negative correlation between scoliosis-specific score and number of views ( P = 0.01). Conclusions: Online health information has historically been poor and our study shows that in an environment like YouTube that lacks a peer review process, the quality of scoliosis information is low. Further work is needed to determine whether accessing information on YouTube can play a role in patient care other than simple education pertaining to the disease and its management. Level of Evidence: 3 Abstract : Supplemental Digital Content is available in the text